2022
DOI: 10.1038/s41598-022-25654-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of cerebral white matter hyperintensities with coronary artery calcium in a healthy population: a cross-sectional study

Abstract: In brain magnetic resonance imaging (MRI), white matter hyperintensity (WMH) is a commonly encountered finding and is known to reflect cerebral small vessel disease. The aim of our study was to investigate the association of coronary artery calcium (CAC) with WMH and elucidate the relationship between WMH and atherosclerotic risk factors in a large-scale healthy population. This retrospective study included 1337 individuals who underwent brain MRI and CAC scoring computed tomography at healthcare centers affil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Our results are of interest as previous studies led to speculations about the mechanisms behind the association of cerebral WMH—a hallmark feature of cerebral small vessel disease—and (subclinical) large vessel atherosclerosis such as CAC 8 11 . A combination of shared classical vascular risk factors (predominantly arterial hypertension) and a genetic predisposition was suspected behind this phenomenon 8 11 . In this context, Johansen et al identified differences in the strengths of the relationship between CAC and different WMH subtypes 9 .…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Our results are of interest as previous studies led to speculations about the mechanisms behind the association of cerebral WMH—a hallmark feature of cerebral small vessel disease—and (subclinical) large vessel atherosclerosis such as CAC 8 11 . A combination of shared classical vascular risk factors (predominantly arterial hypertension) and a genetic predisposition was suspected behind this phenomenon 8 11 . In this context, Johansen et al identified differences in the strengths of the relationship between CAC and different WMH subtypes 9 .…”
Section: Discussionmentioning
confidence: 73%
“…As atherosclerotic large vessel disease results in the stiffening of arteries, it is hypothesized that the subsequent increase in blood-flow pulsatility within the brain-supplying vessels directly damages the small cerebral vasculature, thereby promoting WMH 9 , 12 , 13 . For this reason, CAC was assumed to predict cerebral WMH progression, but previous studies only had cross-sectional data available 8 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations